EPIDEMIOLOGICAL STUDY OF ILEAL PERFORATION IN PATIENTS PRESENTING TO TERTIARY CARE CENTRE IN NORTH-WEST RAJASTHAN - ALLA, SONALI; CHOUDHARY, RENUKA; MIDDHA, SAHIL; SALIM, MOHD (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: We organized an investigation to study epidemiology and various factors affecting morbidity and mortality of ileal perforation. Methods: This study is a hospital-based prospective and descriptive study of patients admitted from November 2020 to October 2021. Fifty patients of ileal perforation who were admitted in P.B.M. Hospital during this period have been included in the study. Results: Typhoid fever accounting for 34% of total cases, 42% were treated by ileostomy, 34 had complications. Out of 50 cases, 34 had complications around half cases had wound dehiscence. Ileostomy was the most common (n=21, 42%) surgical procedure done in cases of ileal perforation. Wound dehiscence was the most common (n=19, 55.88%) post-operative complication observed among study subjects. Conclusion: Early diagnosis is essential since a proper diagnosis and its therapy are essential to the prognosis. Traumatic perforations have a positive outcome since the lag time is usually short. The kind of surgery performed has no effect on the death rate; however, stoma development is linked to less problems.